On the Definition of Technical Terms and Terminological Dictionaries - Abdullaeva Fotima Bakhromovna, Rasulova Zukhra Bakhromovna, Isarov Oman Risaliyevich (International Journal of Advanced Science and Technology, 2020)
The article analyzes the existing shortcomings and flaws in the field of linguistics, in particular, the definition of technical terms and the problems related to terminological dictionaries. Such concepts as professional words, professionalisms, special vocabulary, terminological system, terminological lexicon, technical terminology are elucidated and the differences among them are singled out. The authors’ personal definition for the technical term has also been formulated.